PAI-1 gene 4G/5G polymorphism, cytokine levels and their relations with metabolic parameters in obese children - Kinik, Sibel Tulgar; Özbek, Namik; Yuce, Muammer; Yazici, Ayse Canan; Verdi, Hasibe; Ataç, F. Belgin (Thrombosis and Haemostasis, 2008)
Obesity is associated with the changes of plasminogen activator inhibitor-1 (PAI-1), tumor necrosis factor-alpha (TNFα) and transforming growth factor beta (TGFβ) levels. However, the precise effect of the 4G allele on obesity is still contradictory. Here, we aimed to elucidate the role of the 4G/5G polymorphism of the PAI-1 gene on the PAI-1 level and determine the associations between cytokines, glucose and lipid metabolism parameters in obese children. Thirty-nine obese children (mean age 11.4 ± 3.3 years) and 38 age-matched healthy control group (mean age 10.3 ± 3.5 years) were included in the study. In all cases, serum levels of glucose, lipid and insulin were measured, homeostasis model assessment of insulin resistance (HOMAIR) was calculated, and 4G/5G polymorphism of PAI-1 gene, plasma PAI-1 level and serum TNFα and TGFβ levels were studied. The mean relative body mass index (BMI) and HOMA-IR score, VLDL,TG, insulin, PAI-1,TNFα levels were higher, and HDL and TGFβ levels were lower in the obese group. The frequency of the 4G/4G genotype was considerably higher in obese children than in controls. Also, a positive correlation was found between PAI-1 and TNFα levels, and relative BMI, HOMA-IR score, insulin,TG, HDL levels. TGFβ was inversely correlated only with relative BMI. There was no correlation among three cytokines. In conclusion, childhood obesity contributes to higher PAI-1 andTNFα and lowerTGFβ levels. Especially PAI-1 andTNFα accompany insulin resistance and dyslipidemia.
Keywords: Childhood obesity; PAI-1 gene 4G/5G polymorphism; cytokines